The working stroke of the myosin II motor in muscle is not tightly coupled to release of orthophosphate from its active site. (29th August 2013) - Caremani, Marco; Melli, Luca; Dolfi, Mario; Lombardi, Vincenzo; Linari, Marco
Key points:   Force and shortening in muscle are caused by ATP‐driven working strokes of myosin II motors, during their cyclic interactions with the actin filament in each half‐sarcomere. Crystallographic studies indicate that the working stroke consists in an interdomain movement of the myosin motor associated with the release of inorganic phosphate (Pi ).   Here the coupling of the working stroke with the release of Pi is studied in situ using fast half‐sarcomere mechanics on skinned fibres from rabbit psoas.   The isotonic velocity transient following stepwise force reductions superimposed on isometric contraction measures the mechanical manifestation of the working stroke and its rate of regeneration.   The results indicate that the release of Pi from the catalytic site of an actin‐attached myosin motor can occur at any stage of the working stroke, and a myosin motor uses two consecutive actin monomers to maximize the power during shortening. Abstract  Skeletal muscle shortens faster against a lower load. This force–velocity relationship is the fundamental determinant of muscle performance in vivo and is due to ATP‐driven working strokes of myosin II motors, during their cyclic interactions with the actin filament in each half‐sarcomere. Crystallographic studies suggest that the working stroke is associated with the release of phosphate (Pi ) and consists of 70 deg tilting of a light‐chain domain that connects the catalytic domain of the myosin motor to the myosin tail and filament. However, the coupling of the working stroke with Pi release is still an unsolved question. Using nanometre–microsecond mechanics on skinned muscle fibres, we impose stepwise drops in force on an otherwise isometric contraction and record the isotonic velocity transient, to measure the mechanical manifestation of the working stroke of myosin motors and the rate of its regeneration in relation to the half‐sarcomere load and [Pi ]. We show that the rate constant of the working stroke is unaffected by [Pi ], while the subsequent transition to steady velocity shortening is accelerated. We propose a new chemo‐mechanical model that reproduces the transient and steady state responses by assuming that: (i) the release of Pi from the catalytic site of a myosin motor can occur at any stage of the working stroke, and (ii) a myosin motor, in an intermediate state of the working stroke, can slip to the next actin monomer during filament sliding. This model explains the efficient action of muscle molecular motors working as an ensemble in the half‐sarcomere.